RANCANG ULANG PENGENDALIAN MUTU PRODUK PADA INDUSTRI KOMPONEN SEPEDA MOTOR MENUJU ZERO DEFECT UNTUK MENCAPAI OPTIMALISASI MANUFAKTUR - Dahniar, Tedi (Jurnal TAMBORA, 2017)
PT. Indonesia Nippon Seiki is a manufacturing company that has been implementing quality control system, not necessarily achieve zero defect. This study aims to improve the quality control system to zero defect. The study was conducted on a company that produces two-wheeled automotive parts. The research applied Failure Methode and Effect Analysis (FMEA) method to identify the main problem of product defect, its cause and its impact. FMEA is conducted using 3 years production data on 3 assembly plants with field observation and interviews with key personnel in each factory. The results showed that the improvement needs to be done on the elements of the machine, human, methods and environment, after the improvement is done on the four elements of the product failed or reject and claim can be derived.